Answer:
Simplifying
lx2 + mx + n = 0
Solving
lx2 + mx + n = 0
Solving for variable 'l'.
Move all terms containing l to the left, all other terms to the right.
Add '-1mx' to each side of the equation.
lx2 + mx + -1mx + n = 0 + -1mx
Combine like terms: mx + -1mx = 0
lx2 + 0 + n = 0 + -1mx
lx2 + n = 0 + -1mx
Remove the zero:
lx2 + n = -1mx
Add '-1n' to each side of the equation.
lx2 + n + -1n = -1mx + -1n
Combine like terms: n + -1n = 0
lx2 + 0 = -1mx + -1n
lx2 = -1mx + -1n
Divide each side by 'x2'.
l = -1mx-1 + -1nx-2
Simplifying
l = -1mx-1 + -1nx-2
Step-by-step explanation:
Hope this helped you!
Ok??????????????????????????
Answer:
c = 3 c = -1/2
Step-by-step explanation:
(4c-5)^2= 49
Take the square root of each side
sqrt((4c-5)^2)= ±qrt(49)
4c-5 = ±7
Separate into two equations
4c-5 = 7 4c-5 = -7
Add 5 to each side
4c-5+5 = 7+5 4c-5+5 =-7+5
4c =12 4c = -2
Divide by 4
4c/4 = 12/4 4c/4 = -2/4
c = 3 c = -1/2
Answer:
I think the answer iss ( -∞ , -1] ∪ ( -1/2, +)
Step-by-step explanation:
(ノ◕ヮ◕)ノ*:・゚✧ ✧゚・: *¯\_(ツ)_/¯